2000
DOI: 10.1046/j.1440-1746.2000.02163.x
|View full text |Cite
|
Sign up to set email alerts
|

K‐ras codon 12 mutations in Barrett’s oesophagus and adenocarcinomas of the oesophagus and oesophagogastric junction

Abstract: These results suggest that K-ras codon 12 mutations may occur frequently in patients with Barrett's oesophagus with high-grade dysplasia or adenocarcinoma of the oesophagus or oesophagogastric junction. K-ras mutation may be a late event in the Barrett's metaplasia-dysplasia-adenocarcinoma sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 34 publications
2
38
0
1
Order By: Relevance
“…Reports at point mutations in K-Ras in Barrett's esophagus and in esophageal adenocarcinomas showed them to be rare [50][51][52]. Another report described K-Ras mutations in 0% of Barrett's metaplasias, 0% of low grade dysplasias, 30% of high grade dysplasias, and 40% of adenocarcinomas [53]. Activation of the Ras proto-oncogenes seems to be of little importance in Barrett's adenocarcinomas.…”
Section: Growth Factors and Their Receptorsmentioning
confidence: 99%
“…Reports at point mutations in K-Ras in Barrett's esophagus and in esophageal adenocarcinomas showed them to be rare [50][51][52]. Another report described K-Ras mutations in 0% of Barrett's metaplasias, 0% of low grade dysplasias, 30% of high grade dysplasias, and 40% of adenocarcinomas [53]. Activation of the Ras proto-oncogenes seems to be of little importance in Barrett's adenocarcinomas.…”
Section: Growth Factors and Their Receptorsmentioning
confidence: 99%
“…Recent data have shown that B-raf is mutated in about 7% of cancers, identifying it as another important oncogene on this pathway [11]. The highest incidence of B-raf mutations is in malignant melanoma (27%-70%), papillary thyroid cancer [15] (36%-53%), colorectal cancer [18] (5%-22%), and ovarian cancer (30%), but they also occur at a low frequency (1%-3%) in a wide variety of other cancers, including stomach cancer [14], squamous cell carcinomas of the head and neck, and lung cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…58 Recently, studies have demonstrated K-ras mutations in 11% to 40% of esophageal adenocarcinomas, but few data are available on the frequency of Ras mutations in gastric cardia adenocarcinomas. 57,59 Moreover, available data do not support an important role for oncogenic B-raf in adenocarcinomas of the upper gastrointestinal tract. 57,60,61 Given the pivotal role of Ras proteins in the regulation of cell growth, it is not surprising that inhibitors of Ras are in development as anticancer therapies.…”
Section: Independence From Exogenous Stimulationmentioning
confidence: 99%